Genetic and toxigenic diversity of Bacillus cereus group isolated from powdered foods (2021)
ABSTRACT : Bacillus cereus is a human pathogenic bacterium that produces emetic and diarrheal foodborne diseases. This study evaluated the genetic and toxigenic diversity in B. cereus group isolates from powdered foods collected in public educational institutions, bakeries and powdered food companies located in Medellı´n, Colombia. B. cereus was detected in 35 of 305 (11%) powdered food samples and 52 B. cereus were isolated. The presence of ten toxin genes, hblCDAB, nheABC, cytK2, entFM and cesB, was evaluated in the isolates by multiplex PCR. The nheABC operon was found in all isolates (100%), hblCDAB in 22 (42%), hblCDA in 8 (15%) and hblCD in 3 (6%); the cytK2 gene was detected in 32 isolates (62%) and entFM in 32 (62%). Notably, the cesB gene was not detected. According to the presence of toxin genes, fifteen profiles were identified. The predominant toxigenic profile contained all toxin genes but cesB. A large genetic diversity was observed by GTG5 fingerprinting with 46 isolates grouped in seven clusters and the remaining six clustering individually. There was no relationship between toxigenic profiles and genetic clusters, but some genetic clusters seemed to be related to particular powdered food types. In general, the results evidenced high genetic and enterotoxigenic diversity among the B. cereus group isolates.